PWE-166 Is Response To Linaclotide After 4 Weeks Of Treatment Predictive Of 12-week Improvement?. (9th June 2014) - Chey, W; Lavins, B; Shiff, S; MacDougall, J; Kurtz, C; Currie, M; Johnston, J
Abstract : Introduction: Linaclotide is a minimally absorbed guanylate cyclase C agonist approved in the US and EU for irritable bowel syndrome with constipation (IBS-C). A question for prescribing physicians is whether to continue linaclotide in patients who do not improve during the early weeks of therapy. This post-hoc analysis assessed if response to linaclotide at Week 4 predicts Week 12 improvement, and if linaclotide should be continued in IBS-C patients not responding by Week 4. Methods: Pooled data from 2 Phase 3 IBS-C trials of linaclotide were analysed. For Degree of Relief of IBS Symptoms, Degree of Relief of Abdominal Pain, and Spontaneous Bowel Movement [SBM] frequency, a patient's Week-4 clinical response was used to predict improvement at Week 12. For the purposes of determining a patient's Week-4 response, the 7-point balanced Degree of Relief scale was collapsed into 3 categories: Improved (completely, considerably, or somewhat relieved), Unchanged, and Worse (somewhat worse, considerably worse, or as bad as I can imagine) compared with baseline. For SBM frequency, a dichotomous end point was used: SBMs increased by ≥2/week or not increased by ≥2/week from baseline. Results: The proportion of patients who had response at Week 4 was significantly greater for linaclotide- vs placebo-treated patients: 72 vs. 47% for Degree of Relief of IBS Symptoms, 70 vs. 47% for Degree of Relief of Abdominal Pain, and 59% vs 33% for SBM frequency (all comparisons: p < 0.0001). For all parameters, most linaclotide-treated patients (≥70%) who had response at Week 4 were improved at Week 12. For linaclotide-treated patients whose symptoms were unchanged at Week 4 for Degree of Relief of IBS Symptoms and Degree of Relief of Abdominal Pain, 36 and 39% were improved at Week 12, vs. 19 and 21% of the placebo group, respectively (p < 0.05). For SBM frequency, 30% of linaclotide-treated patients vs. 17% of placebo-treated patients without response at Week 4 were improved (SBMs ≥2) at Week 12 (p < 0.05). Conclusion: Patients whose IBS symptoms improved after 4 weeks with linaclotide were likely to maintain improvement. At least 30% of linaclotide patients who were unchanged at Week 4 experienced symptom improvement by Week 12. The significant differences between linaclotide and placebo in the percentage of patients improved at Week 12 who were unchanged at Week 4 indicates that in some patients ≥1 month of linaclotide therapy may be required for improvement. Hence, an initial course of linaclotide therapy in patients with IBS-C shou.ld be >4 weeks. Study funded by Forest Laboratories, Inc., and Ironwood Pharmaceuticals, Inc. Disclosure of Interest: W. Chey Consultant for: Ironwood Pharmaceuticals, Forest Research Institute, B. Lavins Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, S. Shiff Shareholder of: Forest Research Institute, Employee of: Forest Research Institute, J. MacDougall Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, C. Kurtz Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, M. Currie Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, J. Johnston Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals.